2006
DOI: 10.1074/jbc.m601658200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of 2-Nitropropane Dioxygenase Complexed with FMN and Substrate

Abstract: Nitroalkane compounds are widely used in chemical industry and are also produced by microorganisms and plants. Some nitroalkanes have been demonstrated to be carcinogenic, and enzymatic oxidation of nitroalkanes is of considerable interest. 2-Nitropropane dioxygenases from Neurospora crassa and Williopsis mrakii (Hansenula mrakii), members of one family of the nitroalkane-oxidizing enzymes, contain FMN and FAD, respectively. The enzymatic oxidation of nitroalkanes by 2-nitropropane dioxygenase operates by an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…This study aimed to characterize PA1024, one of the three genes encoding a hypothetical NMO in P. aeruginosa PAO1. The current classification of PA1024 is based on a 2006 study (7), but the enzyme does not carry the consensus motifs characteristic of the recently defined class I and class II NMOs (6). The biochemical and kinetic characterization of PA1024 presented herein shows that the enzyme indeed is not an NMO, as indicated by the lack of oxygen consumption with propionate-3-nitronate and other nitronates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study aimed to characterize PA1024, one of the three genes encoding a hypothetical NMO in P. aeruginosa PAO1. The current classification of PA1024 is based on a 2006 study (7), but the enzyme does not carry the consensus motifs characteristic of the recently defined class I and class II NMOs (6). The biochemical and kinetic characterization of PA1024 presented herein shows that the enzyme indeed is not an NMO, as indicated by the lack of oxygen consumption with propionate-3-nitronate and other nitronates.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate this hypothesis, we experimentally tested NADH, NADPH, and various quinones for catalytic activity. Furthermore, we reanalyzed and modified the conserved motifs identified by Ha et al (7) in the protein sequence of PA1024, and we showed that they are present in more than 490 sequences in the non-redundant protein database. The results reinforce the need for accurate experimental data on select hypothetical proteins to work in concert with computational methods for improved gene function prediction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is essential for fatty acid synthesis and hence a potential target for the drugs against tuberculosis. The structure of Mycobacterium tuberculosis 2NPD enzyme is unknown [5,6].…”
Section: Target Proteinmentioning
confidence: 99%